Crocidura hikmiya, a new shrew (Mammalia: Soricomorpha: Soricidae) from Sri Lanka - Meegaskumbura, Suyama; Meegaskumbura, Madhava; Pethiyagoda, Rohan; Manamendra-Arachchi, Kelum; Schneider, Christopher J. (Zootaxa, 2007)
A new species of crocidurine shrew, Crocidura hikmiya, is described from the Sinharaja World Heritage Site, Sri Lanka. The species is diagnosed on the basis of both morphology and mitochondrial DNA sequence data. Morphologically C. hikmiya is distinguished from C. miya, among other characters, by having a shorter tail, condyles protruding beyond the margin of the braincase, a posterior edge of maxillary bone rounded (dorsal view), an occipital bone triangularly shaped with an obtuse angle (dorsal view) and slightly flattened on the back; a foramen magnum less deep (ventral view); a dorsal posterior brain case not smooth; and an angular process of dentary short and stout. Phylogenetic analysis suggests that C. hikmiya is the sister-species of C. miya. The uncorrected genetic distance between the two species for the mitochondrial cytochrome-b gene fragment is 9.7–10.1%, suggesting species-level divergence. Crocidura hikmiya is confined to the mid-montane forests and lowland rainforests in the southwestern Sri Lanka, while C. miya is confined to montane forests of the central hills.